The risk of vision loss in contact lens wear and following LASIK. (9th January 2020) - Wu, Yvonne Tzu‐Ying; Ho, Arthur; Naduvilath, Thomas; Lim, Chris; Carnt, Nicole; Keay, Lisa J; Edwards, Katie P; Stapleton, Fiona
Abstract: Purpose: To compare the risk of vision loss following contemporary laser‐assisted in situ keratomileusis (LASIK) with different types and modality of use of contact lenses. Methods: Data from a previously published study were used to derive the incidence of vision loss (≥ 2 line loss of best corrected spectacle acuity) following microbial keratitis for different contact lens types and wearing modality, stratified by duration of lens wear. A literature search on vision loss following LASIK was performed between 2003 and 2019. The prevalence of vision loss at six months post‐surgery was captured from clinical trials published after 2003. A proportion meta‐analysis was applied to derive the prevalence of vision loss following LASIK. A least‐squares fitting of cumulative vision loss (P, /10 000 wearers) over time ( t, years) using an exponential model estimated the years of contact lens wear to which the risk of vision loss with LASIK was equivalent. Results: Vision loss following LASIK occurred in 66 (95% confidence interval [CI] 34–108) per 10 000 wearers. As a conservative estimate based on the lower confidence interval of the estimated equivalent years of contact lens wear, daily wear contact lenses and extended overnight silicone wear hydrogel contact lens need to be worn for 103 (95% [CI] 103–391) and 25 (95% [CI] 25‐79) years respectively, to equal the rate of vision loss equivalent to a one‐off LASIK procedure. Conclusions: The risk of vision loss to the individual is low with either contact lens wear or refractive surgery. Contact lens wear does not pose a higher risk of vision loss than LASIK surgery for the most common wear modalities.